Sustainable Composites: Analysis of Filler–Rubber Interaction in Natural Rubber–Styrene–Butadiene Rubber/Polyurethane Composites Using the Lorenz–Park Method and Scanning Electron Microscopy - De Carvalho, Arthur Pimentel [UNESP]; Dos Santos, Harison Franca [UNESP]; Ribeiro, Gabriel Deltrejo [UNESP]; Hiranobe, Carlos Toshiyuki [UNESP]; Goveia, Danielle [UNESP]; Gennaro, Elmer Mateus; Paim, Leonardo Lataro [UNESP]; Dos Santos, Renivaldo José [UNESP] (MDPI, 2024)
This study examined micronized polyurethane residues as a reinforcing filler in elastomeric composites made from natural rubber (NR) and styrene–butadiene rubber (SBR). Due to growing environmental concerns, this research aimed to find sustainable alternatives to synthetic materials. The results indicated that adding micronized polyurethane improved the mechanical properties of the composites, reinforcing the polymer matrix and increasing the cross-link density as a barrier against solvents. The composites met the requirements for industrial applications, though; at 40 phr of polyurethane filler, material deformation was reduced, indicating saturation. FTIR analysis confirmed the homogeneity of the materials without chemical reactions, while electron microscopy revealed an increase in the number of particles and irregularities with the filler. The composite with 10 phr showed a lower volume loss in abrasion resistance, meeting the standards for soles. The composite with 30 phr of polyurethane achieved the best results without the filler’s saturation and met the footwear industry’s requirements. The results show the potential for sustainable practices in industry using this elastomeric blend.
Keywords: composites; filler–rubber interaction; Lorenz–Park; polyurethane waste; shoe sole